METHODOLOGICAL RECOMMENDATIONS FOR PARENTS ON THE PREVENTION AND CORRECTION OF FACTORS CONTRIBUTING TO SPEECH DISORDERS IN PRESCHOOL CHILDREN (Web of Teachers: Inderscience Research, 2025)
This article discusses methodological recommendations for parents on the prevention and correction of factors that cause speech disorders in preschool children, as well as the use of fairy tale therapy to eliminate speech disorders in children.